Composite Materials and Advanced Materials Research. - Kim, Jong Hak; Lau, Alan K. T. (: Trans Tech Publications, Limited, 2022)
Selected peer-reviewed extended papers abstracts of which were presented at the 7th International Conference on Composite Materials and Material Engineering (ICCMME), and the 12th International Conference on Advanced Materials Research (ICAMR) Aggregated Book.
Optimization of Continuous Fiber Path Planning for an Additively Manufactured Open-Hole Specimen -- Chapter 6: Materials and Technologies in Construction -- Highlights of Earned Value Analysis in Construction Projects -- Sustainable Concrete with Coconut Fibers to Improve its Mechanical Characteristics in Buildings -- Mechanical Behavior of Low Plasticity Clay Soil Stabilized with Rice Husk Ash -- Self-Sensing Capabilities of Cement Pastes Treated by Direct Current Curing Technique -- Strength Development of LC3 Concrete Containing Grade 100 Ground Granulated Blast-Furnace Slag (GGBFS)
Description based upon print version of record.
Settlement Comparison Research in Response to Gravel Columns with Concrete under a Distributed Vertical Dynamic Load
eBooks on EBSCOhost
Keywords: Materials -- Congresses; Composite materials -- Congresses; Additive Manufacturing; Alloy; Biomedical Materials; Building Materials; Composite; Functional Materials; Materials Forming; Membrane; Nanoparticles; Polymer; Steel; Matériaux -- Congrès.; Composites -- Congrès.; Composite materials; Materials; Conference papers and proceedings